Virtual reality to assess and train team ball sports performance: A scoping review - Faure, C.; Limballe, A.; Bideau, B.; Kulpa, R. (Journal of Sports Sciences, 2020)
Virtual reality (VR) is a widespread technology drawing an increasing interest for players and coaches, especially in team ball sports as it offers a simple tool to simulate, analyse and train situations that are often too complex to reproduce in the field. In this review we aimed at (1) providing an overview of methodologies and outcomes of research studies using VR in team ball sports; (2) better evaluating the potential interest of VR to analyse or train team ball sports situation and (3) identifying limitations, gaps in knowledge and remaining scientific challenges. The MEDLINE and Web of Science Core Collection databases were searched, using predefined combinations of keywords. Thirty articles were retained and analysed. VR can be an interesting tool to assess or train team ball sports skills/situations as it allows researchers to control and standardise situations and focus on specific skills/subskills. Studies that used VR in team ball sports still have some limitations, mainly due to technical issues or study design. This paper also describes the way VR should be used to enhance understanding of performance in team ball sports. Additional suggestions for future research and study design are proposed.